The art of effective communication - Farr, J. Michael; Baker, Bill; Hall, Dan; JIST Works Inc.; JIST Publishing Inc. (Indianapolis, IN : JIST Publishing Inc., 2000)
Covers essential communications skills for work, social and personal situations
Program content has been based on research and writing by J. Michael Farr
Producer, Bill Baker, Kelli Lawrence; writer, Denise Reiter; production, Dan Hall, Bill Baker
Keywords: Communication; Business communication; Interpersonal communication; Oral communication; Written communication